2021
DOI: 10.1097/mog.0000000000000794
|View full text |Cite
|
Sign up to set email alerts
|

Can SARS-CoV-2 be transmitted via faeces?

Abstract: Purpose of review COVID-19 patients can present gastrointestinal symptoms, being diarrhoea one of the most frequent, suggesting intestinal health can be impacted by COVID-19. Here, we will discuss whether there is a correlation between the presence of SARS-CoV-2 RNA in faeces and diarrhoea, the relevance of gastrointestinal symptoms in disease diagnosis and transmission, and how COVID-19 can impact the gut microbial balance. Recent findings SARS-CoV-2 RNA has been reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 29 publications
(103 reference statements)
0
13
0
1
Order By: Relevance
“…In addition, a case report from an autopsy of a young individual acutely infected with SARS-CoV-2 detected the presence of spike protein in intestinal cells ( Mayordomo-Colunga et al, 2021 ). Similarly, it is established that the virus can be detected in feces, and possibly spread through fecal contamination ( Moura et al, 2022 ), although there are no data yet as to whether there is persistent viral shedding in long-COVID patients. What is certain is that gastrointestinal symptoms persist in PASC and that there is significant disruption of the intestinal microbiome from acute and possibly chronic infection with SARS-CoV-2 ( Roy et al, 2021 ).…”
Section: Metabolic Dysfunction and Pascmentioning
confidence: 99%
“…In addition, a case report from an autopsy of a young individual acutely infected with SARS-CoV-2 detected the presence of spike protein in intestinal cells ( Mayordomo-Colunga et al, 2021 ). Similarly, it is established that the virus can be detected in feces, and possibly spread through fecal contamination ( Moura et al, 2022 ), although there are no data yet as to whether there is persistent viral shedding in long-COVID patients. What is certain is that gastrointestinal symptoms persist in PASC and that there is significant disruption of the intestinal microbiome from acute and possibly chronic infection with SARS-CoV-2 ( Roy et al, 2021 ).…”
Section: Metabolic Dysfunction and Pascmentioning
confidence: 99%
“…Individuals infected with SARS-CoV-2 exhibit gastrointestinal symptoms including diarrhea, nausea, vomiting, and abdominal pain. This observation also points to the possibility that SARS-CoV-2 is an enteric virus (Ding and Liang, 2020;Moura et al, 2022). There is a report of persistent virus shedding by children through feces after their nasopharyngeal swabs tested negative for viral RNA (Xu et al, 2020b).…”
Section: Transmission Routesmentioning
confidence: 79%
“…Although we did not find direct evidence for transmission of the virus between the owner and the dog in this case, it has been reported that SARS-CoV-2 has repeatedly spilled over from humans to companion animals, highlighting the need for enhanced surveillance in animals. It is concerning that companion animals could become reservoir species of SARS-CoV-2 since they are susceptible to infection and could excrete infectious virus [12].…”
Section: Resultsmentioning
confidence: 99%